Overview of automatic stuttering recognition system - Lim, Sin Chee; Ooi, Chia Ai; Sazali, Yaacob (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.